Clausewitz's timeless trinity a framework for modern war - Fleming, Colin M. (Military Strategy and Operational Art, 2013)
Building on the existing corpus of scholarship, this is the first book to apply the Clausewitzian Trinity of 'passion, chance, and reason' to the experience of real war. It explores the depth and validity of the concept against the conflicts of former Yugoslavia - wars thought to epitomise a post-Clausewitzian age. In doing so it demonstrates the timeless message of the Trinity, but also ties the Trinitarian idea back into Clausewitz's political argument